Culture Strategy of Baha’is: Case Study in Pati, Central Java, Indonesia - Rosyid, Moh; Kushidayati, Lina (Universitas Sebelas Maret, 2021)
This article based on research carried out in 2021 among the Baha'i religious community in the village of Cebolek Kidul, District Margoyoso, Pati regency, Central Java. Baha’i is an independent religion although sometime people mistaken as a religious sect. Baha’i was first known in Persia in 1840s and came to Indonesia in 1870 brought by medical experts joint a UN’s program and merchants. Data of this article were collected through interviews, observations, documentations and focus group discussion. In Cebolek, there are 25 people of 9 families who observe Baha’i. The contributing factors to the consistency of the Baha'is in Pati (1) understand the meaning of prayer and worship, (2) the Bahai declarator, Mirza Husein, has the title Baha'u'llah who is believed to be a descendant of the saint, (3) Baha'i teachings have no conflict with the principles of humanity, (4) the Baha'i were inspired by the Baha'ullah spirit which was opposed by the religious community which previously existed (Islam) in Persia (Iran) from the beginning he spread his religion. The Bahai people face this opposition as a consequence, (5) the Baha’i people realize that the Baha’i experienced a phase of development through the stages of majhuliyah (unknown period), maqhuriyah (a period of opposition / hindrance), infisoliyah (a period of isolation /separation) with the majority community, istiqlaliyah (period of deliverance), rosmiyah (period of legalization / inauguration), gholabiyah (period of victory), and dzahabiyah (golden period).Keywords: